Pengembangan Media Pembelajaran Power Point Interaktif Dilengkapi Animasi 2D Bahasa Jepang Untuk Meningkatkan Keterampilan Berpikir Kritis Siswa Kelas XI Jurusan Keperawatan di SMK Surya Medika Singaraja - Ni Putu Winda Tya Ariantari; Desak Made Sri Mardani; Ni Nengah Suartini (STKIP AGAMA HINDU SINGARAJA, 2023)
This study aims to develop media in the form of interactive PowerPoint with 2D animation. The purpose of developing this media is to improve students' critical thinking skills. This research is a Research and Development (R&D) study. The development model used is Four-D (4D) by Thiagarajan, et al (1974: 5) which has four (4) stages, namely Define, Design, Develop, Disseminate. The type of data used is qualitative and quantitative data. Data collection was carried out using the interview method and providing questionnaires in the form of expert test questionnaires (media expert test, material expert test) and product trials in order to produce a good product. The resulting media consists of 9 learning materials that contain vocabulary introduction, questions, conversations, and exercises. Based on the results of the questionnaire, the score obtained from the media expert test was 98.52 (very appropriate), from material experts, namely 91.66 (very appropriate). Then the score obtained from the results of the trial questionnaire with the teacher was 98.43 (very appropriate), as well as the limited trial with ten (10) class XI students majoring in nursing, namely 96% (very feasible). Thus, the developed interactive power point media equipped with 2D animation can be used as a support for learning Japanese, can attract students' interest in learning Japanese, and can improve students' critical thinking skills.